Training of Primary Chicken Monocytes Results in Enhanced Pro-Inflammatory Responses - Michel B. Verwoolde; Robin H. G. A. van den Biggelaar; Jürgen van Baal; Christine A. Jansen; Aart Lammers (Veterinary Sciences, 2020)
Beta-glucan-stimulated mammalian myeloid cells, such as macrophages, show an increased responsiveness to secondary stimulation in a nonspecific manner. This phenomenon is known as trained innate immunity and is important to prevent reinfections. Trained innate immunity seems to be an evolutionary conserved phenomenon among plants, invertebrates and mammalian species. Our study aimed to explore the training of primary chicken monocytes. We hypothesized that primary chicken monocytes, similar to their mammalian counterparts, can be trained with β-glucan resulting in increased responses of these cells to a secondary stimulus. Primary blood monocytes of white leghorn chickens were primary stimulated with β-glucan microparticulates (M-βG), lipopolysaccharide (LPS), recombinant chicken interleukin-4 (IL-4) or combinations of these components for 48 h. On day 6, the primary stimulated cells were secondary stimulated with LPS. Nitric oxide (NO) production levels were measured as an indicator of pro-inflammatory activity. In addition, the cells were analyzed by flow cytometry to characterize the population of trained cells and to investigate the expression of surface markers associated with activation. After the secondary LPS stimulation, surface expression of colony stimulating factor 1 receptor (CSF1R) and the activation markers CD40 and major histocompatibility complex class II (MHC-II) was higher on macrophages that were trained with a combination of M-βG and IL-4 compared to unstimulated cells. This increased expression was paralleled by enhanced NO production. In conclusion, this study showed that trained innate immunity can be induced in primary chicken monocytes with β-glucan, which is in line with previous experiments in mammalian species. Innate immune training may have the potential to improve health and vaccination strategies within the poultry sector.